Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Pemerintah Kabupaten Langkat - Ainiel Riany Putri; Agus Tripriyono; Fitri Yani Panggabean (Economic Reviews Journal, 2025)
This research aims to analyze the financial performance of the Langkat Regency Government using a financial ratio analysis approach. The methods used include regional financial independence ratios, effectiveness ratios, efficiency ratios, activity ratios and growth ratios. The data analyzed is in the form of the Langkat Regency Government Budget Realization Report (LRA) for a certain period. The research results show that the level of regional financial independence is still in the low category, which reflects dependence on central government transfers. Apart from that, the regional revenue effectiveness ratio is in the quite good category, but the efficiency ratio shows that there is room for improvement in regional expenditure management. The growth ratio also reflects an increase, although not evenly across all sectors. Based on the results of this analysis, strategic steps are needed to increase regional independence through optimizing the potential for local original income and more efficient budget management. This research makes an important contribution in providing a comprehensive picture of the financial performance of the Langkat Regency Government and provides policy recommendations for better financial management.